2011
DOI: 10.1186/1476-511x-10-245
|View full text |Cite
|
Sign up to set email alerts
|

Krill oil attenuates left ventricular dilatation after myocardial infarction in rats

Abstract: BackgroundIn the western world, heart failure (HF) is one of the most important causes of cardiovascular mortality. Supplement with n-3 polyunsaturated fatty acids (PUFA) has been shown to improve cardiac function in HF and to decrease mortality after myocardial infarction (MI). The molecular structure and composition of n-3 PUFA varies between different marine sources and this may be of importance for their biological effects. Krill oil, unlike fish oil supplements, contains the major part of the n-3 PUFA in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
1
18
0
1
Order By: Relevance
“…Moreover, increased endocannabinoid levels, as metabolic parameters of metabolic syndrome and obesity [136], have been found to be ameliorated in obese rats, mice and humans after KO supplementation [44,45,57,69]. Other recent studies have demonstrated that KO improves memory function, protects against heart failure and attenuates inflammation in ulcerative colitis in rats [46,65,74]. …”
Section: Health Effects Of Non-marine and Marine Plsmentioning
confidence: 99%
“…Moreover, increased endocannabinoid levels, as metabolic parameters of metabolic syndrome and obesity [136], have been found to be ameliorated in obese rats, mice and humans after KO supplementation [44,45,57,69]. Other recent studies have demonstrated that KO improves memory function, protects against heart failure and attenuates inflammation in ulcerative colitis in rats [46,65,74]. …”
Section: Health Effects Of Non-marine and Marine Plsmentioning
confidence: 99%
“…Although more researches are needed to confirm the high bioavailability of KO, its bioactivities are evident. Hitherto, inhibition of hepatic steatosis (Tandy et al 2009), antiinflammation (Deutsch, 2007;Grimstad et al 2012), antioxidation (Grimstad et al 2012), anti-hyperlipidemic effect (Li et al 2013;Tillander et al 2014), antihyperglycemic effect (Tandy et al 2009), improving memory and cognitive function (Konagai et al 2013) and cardioprotective effect (Fosshaug et al 2011) of KO have been observed.…”
Section: Introductionmentioning
confidence: 98%
“…Krill oil is obtained from a tiny shrimp-like species, called Euphausia superba that lives in the Southern Ocean circling Antarctica. A wide range of articles describe the health benefits of krill oil supplementation that depend on a well-defined product and omega-3 phospholipid (PL) integrity [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. This implies the importance to be able to accurately identify the krill oil composition and differentiate from other oils.…”
Section: Introductionmentioning
confidence: 99%
“…And if not completely removed during production, trimethylamine N-oxide (TMAO, an osmolyte and protein stabilizer) as well as homarine (N-methyl picolinic acid) can be detected. Moreover, krill oil contains copper-2 ions coming from hemocyanin that serve as oxygen binders in many crustaceans [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%